Population trends of the fan mussel Pinna nobilis from Portofino MPA (Ligurian Sea, Western Mediterranean Sea) before and after a mass mortality event and a catastrophic storm. Issue 1 (1st January 2021) - Betti, F.; Venturini, S.; Merotto, L.; Cappanera, V.; Ferrando, S.; Aicardi, S.; Mandich, A.; Castellano, M.; Povero, P.
Abstract: Two Pinna nobilis populations thriving inside the borders of the Portofino Marine Protected Area (MPA) (Ligurian Sea, western Mediterranean Sea) were monitored before (2012) and after (September 2018) a dire mass mortality event that, since September 2016, spread through the whole Mediterranean Sea. In Portofino MPA, recorded mortality rates reached values of 91.29% and 43.94% in the two populations. The presence of a Haplosporidium protozoan parasite, considered to be the main cause of the mortality episodes, was confirmed from histological evidence: sporocysts and plasmodia were observed in all the tubules of the digestive glands of the collected specimens. Moreover, a catastrophic storm hit the Ligurian coasts at the end of October 2018, causing considerable damages both below and above the surface; a new survey conducted in November 2018 showed the complete annihilation of the two studied populations, as a probable combination of the continued parasite infections and the mechanical impacts caused by the storm. Finally, in June 2020 the sites were monitored again looking for traces of recovery, but no new specimens were recorded, indicating that P. nobilis became virtually absent from the MPA.